(untitled) (International Journal of Advanced Research in Science, Management and Technology, 2015)
Data deduplication is one of the important data compression techniques for eliminating duplicate copies of repeating data and has been widely used in cloud storage in order to minimize the amount of storage space and save bandwidth. On the other hand, there have been recently wide privacy considerations as data could come in contact with those third party servers also to unauthorized parties. To protect the confidentiality of important data while supporting deduplication, the convergent encryption technique has been proposed to encrypt the data before outsourcing. Different from traditional deduplication systems, the differential privileges of users are further considered in duplicate check beside the data itself. In this review we report a prototype of proposed authorized duplicate check scheme and conduct tested experiments using various prototype and tries to minimize the data duplication that occurs in hybrid cloud storage by using various techniques.